NILAI TAMBAH KOPI ARABIKA DI KABUPATEN TANA TORAJA - Igods Gabryaldo; Rahim Darma; Mahyuddin Mahyuddin (Universitas Galuh, 2022)
Various efforts have been made by the coffee processing industry to increase the added value of arabica coffee. The research was aimed to analyze the activity in the coffee processing industry which plays a major role in increasing the added value of arabica coffee and calculating the added value of arabica coffee in Tana Toraja Regency. This research was conducted in Mengkendek District, which is an area of Tana Toraja Regency. The sample in this study consisted of the coffee processing industry, namely the Unit Usaha Otonom (UUO) Agribisnis Toraja and Gandangbatu Coffee. Data collection uses survey methods and data is analyzed using qualitative and quantitative approaches. Theories used in data analysis include; (1) Porter method to analyze every activity in the coffee processing industry, (2) Hayami method to calculate the added value of arabica coffee. The results of this study conclude that activities that play a major role in increasing the added value of arabica coffee in Tana Toraja Regency are marketing and sales activities through cooperative relationships and operating activities through processing innovations. The added value of arabica coffee obtained by UUO Agribisnis Toraja is IDR 5,907/kg of green coffee beans and Gandangbatu Coffee gets an added value of IDR 25,729/kg of roasted or ground coffee. The added value obtained was significantly different in the processing of arabica coffee with the dry method and the wet method using the raw material in the form of cherry coffee.Keywords : Hayami method, Porter method, Value activities